2020
DOI: 10.3855/jidc.11974
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of katG, inhA, rpoB and pncA in Mycobacterium tuberculosis isolates from MDR-TB risk patients in Thailand

Abstract: Introduction: Multidrug-resistant tuberculosis (MDR-TB) is commonly found in Thailand especially in the public health region 5, the Western region of Thailand. This study’s aim was to characterize katG, inhA, rpoB and pncA genes in Mycobacterium tuberculosis. Methodology: One hundred strains of Mycobacterium tuberculosis (MTB) were isolated from sputum samples of MDR-TB risk patients in the laboratory of the Office of Disease Prevention and Control 5th Ratchaburi province, Thailand from January to Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…Our report showed that katG gene mutation was found at the rate of 79.7%, in which 95.7% had mutations in katG315 codon and 4.3% harbored mutation in katG365 codon. The percentage of 79.7% for the katG gene mutation was consistent with earlier studies in Thailand (Boonaiam et al 2010) (Suthum et al 2020) and other Southeast Asian Countries (Ismail et al 2016) (Caws et al 2006) (Valvatne et al 2009) (Liu et al 2018) (Cheng et al 2021). The prevalence of katG315 mutation varied according to the geographical region: Southeast Asia (78.4%) (Seifert et al 2015), Vietnam (85.3%) (Hang et al 2019), China (59.4%) (Wu et al 2006), the Netherlands (53%) (Van Soolingen et al 2000), Japan (22%) (Ando et al 2010) and Singapore (26%) (Lee et al 1999).…”
Section: Discussionsupporting
confidence: 91%
“…Our report showed that katG gene mutation was found at the rate of 79.7%, in which 95.7% had mutations in katG315 codon and 4.3% harbored mutation in katG365 codon. The percentage of 79.7% for the katG gene mutation was consistent with earlier studies in Thailand (Boonaiam et al 2010) (Suthum et al 2020) and other Southeast Asian Countries (Ismail et al 2016) (Caws et al 2006) (Valvatne et al 2009) (Liu et al 2018) (Cheng et al 2021). The prevalence of katG315 mutation varied according to the geographical region: Southeast Asia (78.4%) (Seifert et al 2015), Vietnam (85.3%) (Hang et al 2019), China (59.4%) (Wu et al 2006), the Netherlands (53%) (Van Soolingen et al 2000), Japan (22%) (Ando et al 2010) and Singapore (26%) (Lee et al 1999).…”
Section: Discussionsupporting
confidence: 91%
“…This is similar to the study of Namratha W et al, and documented that among, 265 showed AFB positive, and 115 showed AFB negative. 26 In drug susceptibility testing, 7% isoniazid (INH) and 6.3% rifampicin (RIF) resistance which was similar to Krairerk Suthum et al 18 Of 183 (43%) culture positive, 20 RIF-resistant strains (by MGIT 960 array) and in them 25 (14%) isoniazidresistant strains were identified similar to Chao-Ju Chen et al 27 In 425 pulmonary samples (Sputum, Pleural fluid Bronchial alveolar lavage, Endotracheal aspirate samples -CBNAAT Gene Xpert), 158 samples were negative. This study found the rifampicin resistance rate 28%.…”
Section: Discussionmentioning
confidence: 65%
“…For MDRTB Line Probe Assay detection, specimens with smear positive, culture-positive, smearnegative sample were used. 17,18 Cartridge Based Nuclear Acid Amplification test (CBNAAt)…”
Section: Microscopic Examination Zeihl-neelsen Stainingmentioning
confidence: 99%
“…The INH resistance of MTB isolates was frequently associated with a mutant katG gene, while inhA mutations were identified in a small number of INH resistant strains [ 8 ]. Results of custom alignment with the sequenced results using the EPI2ME desktop agent algorithm (ONT) showed more than 95% with over 200 × coverage to virtually cover the complete MTB genome (Fig.…”
Section: Resultsmentioning
confidence: 99%